THE LEGALITY OF DOCUMENTS NEGLIGENTLY AFFIXED WITH FORGED STAMPS - Benny Djaja (Diponegoro Law Review, 2022)
Since the last amendment was in force in 2000, the tariff charged for stamp duty has not been adjusted to suit the most recent monetary value up until Law No. 10 of 2020 on Stamp Duty was issued. In addition to tariff adjustment, the new Law also stipulates the levy of stamp duty on digital documents, which have become increasingly popular used in the recent years, with the expectation of boosting the inflow of State revenue generated from the levy of stamp duty. Nonetheless, the rampant distribution of illegal, forged stamps, aside of inflicting material losses on the State finance due to non-optimum revenue generation, also give rise to uncertainty amongst laypersons with regards to the legality of the document concerned. A document found to have used a forged stamp shall be considered legally equal to an unstamped document, leaving thereupon an obligation due for settlement prior to the document being eligible for use, which should be rectified through an administrative means called “pemeteraian kemudian/subsequent stamp” (nazegelen).